(untitled) (The Research of Medical Science Review, 2024)
The paper examines the problems and solutions for ensuring proper diabetes prevention in populations that cannot be reached easily. Diabetes care is imperative and a progressive public health issue that mainly affects the low-income, rural, and ethnic minorities who lack health insurance and face challenges in healthcare facilities. Such barriers include socioeconomic, geographical, cultural, and language barriers and system/health care barriers. In order to commemorate the paper, a discussion of previous research regarding the incidence of diabetes, medical amenities, and modern methods of control is conducted. Those services have also presented data from other research on the common challenges and assessment of the current attempts towards enhancing care for victims, with the use of community-based interventions, telepracticing medicine, and health-promoting interventions. The paper outlines such interventions as policy change, health-system redesign, and culturally appropriate public health interventions to help minimize inequalities in health and diabetes complication outcomes among underserved groups. The study highlights the need for a specific and effective approach and yields ideas for future studies to improve prevention successfully.